2008
DOI: 10.1128/iai.00759-08
|View full text |Cite
|
Sign up to set email alerts
|

Conditions That Diminish Myeloid-Derived Suppressor Cell Activities Stimulate Cross-Protective Immunity

Abstract: Immunity conferred by conventional vaccines is restricted to a narrow range of closely related strains, highlighting the unmet medical need for the development of vaccines that elicit protection against multiple pathogenic serotypes. Here we show that a Salmonella bivalent vaccine comprised of strains that lack and overproduce DNA adenine methylase (Dam) conferred cross-protective immunity to salmonella clinical isolates of human and animal origin. Protective immunity directly correlated with increased levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 59 publications
2
37
0
Order By: Relevance
“…Previously, the expansion of myeloidderived suppressor cells (i.e. MDSCs) was reported in mice infected with both an aroA mutant and WT Salmonella and these MDSCs inhibited antigen-specific CD4 1 T-cell proliferation [39]. Likewise, CD11b 1 Gr-1 1 inflammatory myeloid cells obtained from RASV-infected MyD88 À/À mice showed suppression against OT-II CD4 1 cell proliferation when there were equivalent numbers of myeloid cells and CD4 1 T cells (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, the expansion of myeloidderived suppressor cells (i.e. MDSCs) was reported in mice infected with both an aroA mutant and WT Salmonella and these MDSCs inhibited antigen-specific CD4 1 T-cell proliferation [39]. Likewise, CD11b 1 Gr-1 1 inflammatory myeloid cells obtained from RASV-infected MyD88 À/À mice showed suppression against OT-II CD4 1 cell proliferation when there were equivalent numbers of myeloid cells and CD4 1 T cells (Supporting Information Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, early studies linked NO-producing macrophage precursors to S. Typhimurium-induced immunosuppression and protective immunity against S. Typhimurium to diminished expansion of CD11b ϩ Gr-1 ϩ cells (16,17). Several recent studies have associated CD11b…”
Section: Ly6cmentioning
confidence: 99%
“…Although immature myeloid cells play a critical role in the protective host response to infection (14), several early studies have linked nitric oxide (NO)-producing macrophage precursors to immunosuppression in salmonellosis (16). Murine immature myeloid cells express surface CD11b and Gr-1 (13) and have been found in spleens of mice infected with S. Typhimurium (17,18).…”
mentioning
confidence: 99%
“…These findings suggest that MDSCs play a role in TB pathogenesis and the increased numbers of these cells in old age may contribute to the reduced immunity to TB in some older adults. Similarly, Heithoff et al (2008) showed that young BALB/c mice immunised with a Salmonella bivalent vaccine developed crossprotective immunity against clinical isolates of salmonella (from humans and farm animals) whereas nonvaccinated mice died 21 days post-infection. In aged C57BL/6 mice, there was a 10-fold increase in the number of bacteria in the spleen compared to young mice and early death of infected aged animals.…”
Section: Infections Mdscs and Ageingmentioning
confidence: 99%